Change Regularity of Taste and the Performance of Endogenous Proteases in Shrimp (Penaens vannamei) Head during Autolysis - Shujian Wu; Mouming Zhao; Shijue Gao; Yue Xu; Xiaoying Zhao; Mingyuan Liu; Xiaoling Liu (Foods, 2021)
This study evaluated the food safety and proximate composition of shrimp head (SH). Potentially toxic elements in SH were below European Union legislation limits. SH had a high content of tasting amino acids (sweet and umami amino acids was 57%) and a high content of functional amino acids (essential amino acids was 37%). Moreover, the changes of flavor and key umami molecules in SH were studied by sensory evaluation, electronic tongue, electronic nose, automated amino acid analyzer, and high performance liquid chromatography (HPLC). The results showed that the significant difference of flavor in SH happened during autolysis. SH with autolysis had the best umami taste at 6 h, which may result from the synergistic work of free amino acids and nucleotide related compounds. Additionally, the performance of endogenous proteases in SH was investigated to efficiently analyze autolysis. The optimum pH and temperature of endogenous proteases in SH were 7.5 and 50 °C, respectively. The autolysis of SH depends on two endogenous proteases (~50 kDa and ~75 kDa). These results suggest that the formation of flavor in SH during autolysis can be controlled, which could provide guidance for SH recycle. SH could consider as one of the food materials for producing condiments.